Comparative metabolic profiling of vetiver (Chrysopogon zizanioides) and maize (Zea mays) under lead stress. (February 2018) - Pidatala, Venkataramana R.; Li, Kefeng; Sarkar, Dibyendu; Wusirika, Ramakrishna; Datta, Rupali
Abstract: Lead (Pb) contamination of residential soils in United States is attributed to use of Pb based paints prior to 1978 and their deterioration and accumulation in surface soils. Exposure to Pb due to ingestion and inhalation of Pb laden soil and dust causes neurological disorders, renal disorders, developmental and behavioral problems, particularly in children under the age of six. Vetiver grass is one of the leading choices for Pb remediation due to its ability to hyperaccumulate Pb, in addition to high biomass. In order to understand the effect of Pb on vetiver metabolic pathways, we compared the global metabolic changes in vetiver with that of maize, a Pb susceptible plant under Pb stress. Vetiver showed massive increase in levels of key metabolites in response to Pb, including amino acids, organic acids and coenzymes. Maize showed very modest increase in some of the same metabolites, and no change in others. The results provide the first indication of the difference in metabolic response of the hyperaccumulator, vetiver to lead stress as compared to maize. Graphical abstract: Image 1 Highlights: The study shows differences in metabolomics of vetiver and maize under lead stress. Massive increase in key metabolites was observed in response to lead. Metabolites showing large increase include amino acids, organic acids and coenzymes. Maize showed modest increase in only a few of the same metabolites.